2017
DOI: 10.1177/1049731517735575
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Fast-Track Postgraduate Social Work Program in England Using Simulated Practice

Abstract: Objective: Using data from our evaluation of the Frontline fast-track social work training program, introduced by the Government in England, we compare the performance of the first cohort of Frontline trainees with students from regular social work programs using simulated practice. Method: Forty-nine Frontline trainees were compared with 36 postgraduate students in high-tariff universities and 30 students from a range of other regular programs. Kruskal–Wallis tests were used to compare the performance of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Twenty studies (38%) explicitly addressed culture and diversity in the study design, curriculum, purpose, instruments, client vignette scenarios, and/or findings. Of the 20 articles explicitly integrating culture, 8 (16%) stated that they used assessment tools that incorporated dimensions of culture and diversity (Carter et al, 2018; Costello et al, 2017; Dennison, 2011; Katz et al, 2014; Lu et al, 2011; Schreiber & Minarik, 2018; Scourfield et al, 2019; Tufford et al, 2017). In three (6%) of these studies, authors stated that elements of culture and diversity were incorporated in curricula or courses that students completed before the simulation session (Manning et al, 2016; Robinson, Thiel, Shirkey, Zurakowski, & Meyer, 2016; Sampson et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Twenty studies (38%) explicitly addressed culture and diversity in the study design, curriculum, purpose, instruments, client vignette scenarios, and/or findings. Of the 20 articles explicitly integrating culture, 8 (16%) stated that they used assessment tools that incorporated dimensions of culture and diversity (Carter et al, 2018; Costello et al, 2017; Dennison, 2011; Katz et al, 2014; Lu et al, 2011; Schreiber & Minarik, 2018; Scourfield et al, 2019; Tufford et al, 2017). In three (6%) of these studies, authors stated that elements of culture and diversity were incorporated in curricula or courses that students completed before the simulation session (Manning et al, 2016; Robinson, Thiel, Shirkey, Zurakowski, & Meyer, 2016; Sampson et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…In 10 studies (19%), simulation was used to assess generalist competencies (Bogo et al, 2013, 2012, 2011; Carrillo & Thyer, 1994; Katz et al, 2014; Lu et al, 2011; Petracchi, 1999; Petracchi & Collins, 2006; Rawlings, 2012; Tufford et al, 2017). The remaining 12 studies used simulation to assess specialized competencies, including suicide risk assessment (Bogo, Regehr, Baird, Paterson, & LeBlanc, 2017; Regehr et al, 2016), social work practice with LGBQQ populations (Logie et al, 2015), depression (Gellis & Kim, 2017), child neglect (Tufford et al, 2015), practice with children and families (Scourfield et al, 2019), screening of suicide and violence (Sampson et al, 2018), risk assessment in child welfare (LeBlanc et al, 2012), domestic violence in health care (MacDonnell et al, 2016), child maltreatment (Regehr et al, 2010), substance use (Sacco et al, 2017), and children’s services (Wilkins et al, 2018). The OSCE was used in 10 of 22 studies (45%; e.g., Bogo et al, 2012; Gellis & Kim, 2017; Katz et al, 2014; Lu et al, 2011; Sampson et al, 2018; Scourfield et al, 2019; Tufford et al, 2015, 2017).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The evaluation data presented illustrated the manner in which social injustice, poverty, and anti-oppressive practice learning was embedded in practice and where the unit provided the space for lively discussion and consideration of the social and economic conditions on families. While findings from a simulated exercise found that Frontline participants were rated higher on cultural competence than their counterparts from mainstream social work courses (see Scourfield et al, 2019).…”
Section: Inputsmentioning
confidence: 99%
“…Assessment of participant learning was captured using a simulated exercise reported elsewhere (see Scourfield et al, 2019). While this comparative analysis demonstrated stronger interviewing and reflection skills than students on mainstream courses, it was unclear the extent to which these results were influenced by the higher prior academic achievements of Frontline participants.…”
Section: Participants' Learningmentioning
confidence: 99%